Women and higher education: Access, equity, and opportunities for women in the workplace - Dosunmu, A. G.; Dichaba, M. (South African Journal of Higher Education, 2024)
Women in corporate sectors across South Africa are not adequately represented. Despite the influx of women in the workforce, they are still experiencing challenges in leadership positions compared to their male counterparts. Thus, the gender gap has caused most women to put extra effort into building their careers through personal efforts ‒ mentorship, networking, and further training. This article analyzed quantitative data and discussed how access to higher education influences career choice and the advancement of women in the telecommunication industry in South Africa. One hundred and thirty-three (133) junior and middle women workers from a telecommunication company were chosen randomly to understand how they plan to build their careers and the challenges they have encountered. The finding indicates that the driving force among the respondents was the opportunities they had created for themselves to progress in their careers.